Comparison of the Effectiveness of Flipbook and Leaflet Media on Gastritis Prevention Behaviors among Junior High School Adolescents in Bulukumba Regency - Darwis, Dian Yuliawati; Haerana, Bs Titi; Tri Addya; Kurniati, Yessy (Unihealth Community Research, 2026)
Gastritis is an inflammation of the gastric mucosa that can occuracutely or chronically and is closely associated with foodborne diseases. Adolescents are a vulnerable group to gastritis, making early prevention through school-based health promotion essential. This study aimed to compare the effectiveness of flipbook and leaflet media on gastritis prevention behaviors among junior high school students in Bulukumba Regency. A quasi-experimental study with a control group pretest–posttest design was conducted involving 131 respondents selected through purposive sampling. Data were collected using structured pretest and posttest questionnaires that had been validated and proven reliable. Statistical analyses were performed using the Wilcoxon test and Kruskal–Wallis test. The results showed improvements in knowledge, attitudes, and practices across all groups after the intervention. Flipbook media were more effective in improving students’ knowledge (mean rank 74.90; p=0.052) and attitudes (mean rank 98.18; p=0.000). In contrast, leaflet media demonstrated greater effectiveness in improving preventive practices (mean rank 75.66; p=0.054). In conclusion, health promotion media significantly influence gastritis prevention behaviors among adolescents. Flipbooks are more effective in enhancing cognitive and affective domains, while leaflets are more effective in improving psychomotor aspects. Strengthening school-based health programs is recommended to promote healthy lifestyles among students.